ANALISIS KEPUASAN PENGGUNA APLIKASI SIAPEL-TEGAS MENGGUNAKAN END USER COMPUTING SATISFACTION (EUCS) DAN PERCEIVED SERVICE QUALITY - Worih Ilhamanto; Ahsanun Khudori; Risqy Pradini (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
SIAPEL-TEGAS is a digital population administration service platform managed by the Population and Civil Registration Office (Dispendukcapil) of Malang City. This study aims to measure user satisfaction with SIAPEL-TEGAS using the End User Computing Satisfaction (EUCS) method, supplemented by a Perceived Service Quality construct. A descriptive quantitative approach was applied to 35 administrators managing cooperation agreements between healthcare facilities and Dispendukcapil Malang City, selected through purposive sampling. Data were collected using a 24-item questionnaire on a 5-point Likert scale, tested for validity (r-count > 0.334) and reliability (Cronbach's Alpha > 0.80). The results show that all dimensions fall within the very satisfied category, with the highest index recorded for Content and Format (89.14%), followed by Perceived Service Quality (88.34%), Ease of Use (88.23%), Accuracy (88.14%), and Timeliness as the lowest index (87.62%). These findings indicate that SIAPEL-TEGAS has met users' technical and functional needs, although continuous improvement in timeliness remains necessary to optimize digital population administration services in Malang City.